CSF Levels of CXCL12 and Osteopontin as Early Markers of Primary Progressive Multiple Sclerosis. Issue 6 (29th November 2021) - Marastoni, Damiano; Magliozzi, Roberta; Bolzan, Anna; Pisani, Anna Isabella; Rossi, Stefania; Crescenzo, Francesco; Montemezzi, Stefania; Pizzini, Francesca Benedetta; Calabrese, Massimiliano
Abstract : Background and Objectives: To evaluate the extent of intrathecal inflammation in patients with primary progressive MS (PPMS) at the time of diagnosis and to define markers and a specific inflammatory profile capable of distinguishing progressive from relapsing-remitting multiple sclerosis (RRMS). Methods: Levels of 34 pro- and anti-inflammatory cytokines and chemokines in the CSF were evaluated at the diagnosis in 16 patients with PPMS and 80 with RRMS. All patients underwent clinical evaluation, including Expanded Disability Status Scale assessment and a 3T brain MRI to detect white matter and cortical lesion number and volume and global and regional cortical thickness. Results: Higher levels of CXCL12 (odds ratio [OR] = 3.97, 95% CI [1.34–11.7]) and the monocyte-related osteopontin (OR = 2.24, 95% CI [1.01–4.99]) were detected in patients with PPMS, whereas levels of interleukin-10 (IL10) (OR = 0.28, 95% CI [0.09–0.96]) were significantly increased in those with RRMS. High CXCL12 levels were detected in patients with increased gray matter lesion number and volume ( p = 0.001, r = 0.832 and r = 0.821, respectively). Pathway analysis confirmed the chronic inflammatory processes occurring in PPMS. Conclusions: At the time of diagnosis, a specific CSF protein profile can recognize the presence of early intrathecal inflammatory processes, possibly stratifying PPMS with respect to RRMS. Elevated CSF levels of CXCL12 and osteopontin suggested a key role of brain innate immunity and glia activity in MS. These molecules could represent useful candidate markers of MS progression, with implications for the pathogenesis and treatment of progressive MS. Classification of Evidence: This study provides Class III evidence that CXCL12 and monocyte-related osteopontin may be correlated with PPMS, and IL-10 may be related to RRMS. It is may be correlated due to Bonferroni correction negating the statistical correlations found in the study.